ANALISIS TENTANG FAKTOR-FAKTOR PENYEBAB PERGESERAN ADAT PERKAWINAN MASYARAKAT JAWA DESA PERKEBUNAN TELUK PANJI KECAMATAN KAMPUNG RAKYAT KABUPATEN LABUHANBATU SELATAN SUMATERA UTARA - Kuntari, Jati; Eddison, Ahmad; ', Zahirman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The implementation of Java traditional wedding in the BayPlantation Village Panji People Kampung District of South Labuhanbatu of NorthSumatra has undergone a change. This study aims to determine what factors are thecause of the shift in the Java community customary marriage Plantation Village PeopleKampung Teluk Panji District of South Labuhan Batu regency of North Sumatra.Respondents in this study were 182 heads of household and 2 elders. Data collectiontechniques are observation, interviews, questionnaires, and documentation. The methodused is the method of combination of quantitative and qualitative (mixed methodes).This method is done with the data processing result data is presented through thecalculation of the percentage and given an explanation. The results showed that thefactors that cause a shift in the Java community customary marriage Plantation VillagePeople Kampung Teluk Panji District of South Labuhanbatu regency of North Sumatrais due to the cultural influence of other communities, contact with other cultures,advanced formal education system, respect for the work of someone and the desire tomove forward, open system of society (open stratification), heterogeneous population,economic factors, time factors, technological factors, and confounding factors tribal/crossbreeding.Key Words: Factor, Shift, Customary Marriages Java